2014
DOI: 10.1097/scs.0000000000000922
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Distraction Osteogenesis With Newly Designed Electromechanical Distractor

Abstract: In this preliminary study, a newly designed electromechanical distractor was successfully used for mandible distraction, which mainly provided a continuous lengthening during activation period spontaneously without any intervention. We think that the clinical application of this electromechanic distractor may provide patient comfort during distraction. Moreover, electromechanical distractor has the potential for high-resolution movement capacity when compared with annual distraction. The promising results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In 2014, a new electromechanical extra-oral ACDO device for enabling continuous DO of mandible was developed [1], and the efficacy of the system was investigated on a sheep model. In this system a DC motor is used for generating the continuous DF.…”
Section: Motor-driven Distractorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, a new electromechanical extra-oral ACDO device for enabling continuous DO of mandible was developed [1], and the efficacy of the system was investigated on a sheep model. In this system a DC motor is used for generating the continuous DF.…”
Section: Motor-driven Distractorsmentioning
confidence: 99%
“…In 2015, the same research group [28], showed that bilateral application of a curvilinear, continuous and automated DO is effective at rate of up to 3 mm/day using a minipig model. In 2014, a continuous DO device was developed and tested on a sheep mandible bone [1]. Macroscopic and radiologic evaluations have shown that the callus was well formed.…”
Section: Continuous Distraction Of the Bone: Proof Of Principlementioning
confidence: 99%
“…c Electronic component of the electromechanical distractor in situ in a sheep model of distraction osteogenesis. ( a , b Reproduced with permission from Burstein; c reproduced with permission from Aykan et al )…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…This has potential risk for human error, especially on repeated applications. Recently, Aykan and co‐workers reported a successful study detailing an electromechanical distractor used for sheep mandibular DO, with an automated distraction phase lasting a total of 20 days ( Fig. ).…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Subsequently, in 1992, MacCarthy reported the first clinical case of a DO procedure on mandible [4–7]. Since then, DO has been widely used as a treatment method to generate the bone, and to fill the skeletal defects, or to correct congenital growth retardation of the bone tissue [5, 8, 9]. In MRA, DO method is a new solution to the tissue lengthening and it is getting a higher clinical attention as a technique without the need for bone graft.…”
Section: Introductionmentioning
confidence: 99%